2020
DOI: 10.1101/2020.06.16.20132597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydroxychloroquine with or without azithromycin and in-hospital mortality or discharge in patients hospitalized for COVID-19 infection: a cohort study of 4,642 in-patients in France

Abstract: Objective To assess the clinical effectiveness of oral hydroxychloroquine (HCQ) with or without azithromycin (AZI) in preventing death or leading to hospital discharge. Design Retrospective cohort study. Setting An analysis of data from electronic medical records and administrative claim data from the French Assistance Publique - Hopitaux de Paris (AP-HP) data warehouse, in 39 public hospitals, Ile-de-France, France. Participants All adult inpatients with at least one PCR-documented SARS-CoV-2 RNA from a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…In our study, the addition of azithromycin to HCQ does not seem to add any clear benefit. A large multicentre observational study reported no association between HCQ, or HCQ with azithromycin, and lower mortality but significantly higher rates of discharge home were observed for patients treated by HCQ [29].…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the addition of azithromycin to HCQ does not seem to add any clear benefit. A large multicentre observational study reported no association between HCQ, or HCQ with azithromycin, and lower mortality but significantly higher rates of discharge home were observed for patients treated by HCQ [29].…”
Section: Discussionmentioning
confidence: 97%
“…Hospital mortality was reported by nine studies [16,20,21,24,26,28,[31][32][33]. Two studies evaluated 28-day mortality [18,27]. Ip et al [22] reported the 30-day and Mahevas et al [25], the 21-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical worsening was reported in six RCTs [12][13][14][15][16][17] and three observational studies. [27,29,32]. Clinical worsening was variously described as development of "severe" illness [12], resolution of fever and improvement in oxygen saturation [14], requirement for hospitalization [17,29] requirement for ICU transfer [27], requirement for mechanical ventilation [32], symptom severity on a 10-point visual analog scale [15], clinical status on a 7-point ordinal scale [16], and alleviation of cough with fever resolution [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations